2017
DOI: 10.2139/ssrn.2993376
|View full text |Cite
|
Sign up to set email alerts
|

Job Mobility and Creative Destruction: Flexicurity in the Land of Schumpeter

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…Some of these studies concurred that selected flexicurity measures increased labour and total factor productivity (Laporšek & Dolenc, 2011;Dolenc & Laporšek, 2013;Muffels & Wilthagen, 2013;Rotar, 2017), while others challenge the flexicurity coordinates as being the main contributors to labour market performance (Andersen & Svarer, 2007). Yet others concluded that flexicurity reforms spur job creation and can substantially reduce unemployment in countries where severance payments are initially high (Kettemann et al, 2017). Differently from others, Seifert and Tangian (2007) bring some empirical evidence for Europe on a possible reconciliation between social security with flexibility and show a positive dependence between aggregate flexibility and aggregate precariousness of work all over Europe.…”
Section: Introductionmentioning
confidence: 98%
“…Some of these studies concurred that selected flexicurity measures increased labour and total factor productivity (Laporšek & Dolenc, 2011;Dolenc & Laporšek, 2013;Muffels & Wilthagen, 2013;Rotar, 2017), while others challenge the flexicurity coordinates as being the main contributors to labour market performance (Andersen & Svarer, 2007). Yet others concluded that flexicurity reforms spur job creation and can substantially reduce unemployment in countries where severance payments are initially high (Kettemann et al, 2017). Differently from others, Seifert and Tangian (2007) bring some empirical evidence for Europe on a possible reconciliation between social security with flexibility and show a positive dependence between aggregate flexibility and aggregate precariousness of work all over Europe.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Austria introduced a reform of severance pay in 2003, which increased flexibility while ensuring income security. Kettemann et al (2017) find that the reform resulted in a substantial increase in job mobility. Portugal introduced an even broader set of reforms between 2011 and 2015 that reduced severance pay and eased the definition of fair dismissal, while widening the safety net and strengthening its activation framework.…”
Section: Country Examplesmentioning
confidence: 87%
“…Reinstatement cannot be imposed on the employer, except in the case of prohibited grounds, such as discrimination. A reform introduced in 2012 has clarified the circumstances under which a layoff can be justified for economic reasons, but judges continue to retain a certain degree of discretion in assessing different cases (Jimeno, Martínez-Matute and Mora-Sanguinetti, 2020 [5]). Insufficient performance, without unsuitability, is not a fair reason for dismissal in Spain.…”
Section: Institutional Backgroundmentioning
confidence: 99%